RELEVANSI MAKNA KATA "KHALIFAH" DALAM KEPEMIMPINAN PENDIDIKAN ISLAM: KAJIAN TAFSIR TEMATIK - ALI RIF’AN; AKHMAD SAID (Piwulang: Jurnal Pendidikan Agama Islam, 2022)
The Qur'an in explaining leadership uses the terminology of “Khalifah, ulu al-amr, imam, and malik”, but the four terms are related to the meaning in accordance with the context of the verse. The scholars' interpretation of the concept of leadership in the Qur'an includes the entire understanding of the leader, the leader of the caliphate, the leader of the prayer, including leadership in the world of education which is often discussed in educational management. This research is a literature study with a study of maudhui interpretations of how the relevance of the meaning of the word “Khalifah” in Islamic education leadership.